Application of Digital Technology to Improve the Quality of Learning in the Era of Revolution 4.0 - Nainggolan, Rafael Owen Kevin; Siboro, Sari Agustina; Ginting, Lentina Nerisa Br. (Edumaniora : Jurnal Pendidikan dan Humaniora, 2024)
In the era of the Fourth Industrial Revolution, digital technology has emerged as a transformative force reshaping the global education landscape. This research aims to examine the application of digital technology in enhancing the quality of learning in the era of Revolution 4.0. Through literature analysis, we explore various ways in which digital technology can be utilized to improve the effectiveness of learning, including the use of online learning platforms, integration of artificial intelligence in the learning process, implementation of augmented reality and virtual reality in learning experiences, and utilization of big data for personalized learning. The research findings indicate that the use of digital technology in education has brought positive impacts in enhancing the quality of learning by improving accessibility, interactivity, and personalization. However, challenges such as access gaps, infrastructure limitations, and integration of technology with traditional curricula remain hurdles that need to be addressed. Therefore, collaborative efforts among governments, educational institutions, and industries are required to optimize the utilization of digital technology in advancing education in the era of Revolution 4.0.